Vertical stratification in foraging activity of the wrinkle-lipped free-tailed bat, chaerephon plicatus (buchanan, 1800) in Central Thailand - Tuan ngoc Nguyen (Prince of Songkla University, 2023)
Master of Science (Ecology (International Program))